Association of family income to poverty ratio and vibration-controlled transient elastography quantified degree of hepatic steatosis in U.S. adolescents - Tang, Meiling; Liu, Mingjiang; Zhang, Ya; Xie, Ruijie (Frontiers in Endocrinology, 2023)
Introduction: Inequality in socioeconomic status plays an important role in the prevalence of metabolic diseases in adolescents. The purpose of this study was to explore the association between family income and the degree of hepatic steatosis quantified by vibration-controlled transient elastography (VCTE) among U.S. adolescents. Methods: This cross-sectional study included two cycles of the National Health and Nutrition Examination Survey (NHANES) 2017-2020. Multivariate linear regression and smoothing curve fitting were used to investigate the linear and nonlinear relationship between PIR and hepatic steatosis, respectively. Subgroup analysis and interaction tests were used to test whether this relationship was stable across groups. Results: Of the 1,574 adolescent participants, 456 lived in poor households and 307 lived in wealthy households. After adjusting for all covariates, PIR (Ratio of family income to poverty) was significantly negatively associated with the degree of hepatic steatosis [-4.78 (-7.39, -2.17)], and this remained stable after converting PIR to a categorical variable. In addition, this significant negative association was more pronounced in women [-7.62 (-11.38, -3.87)], non-Hispanic blacks [-7.19 (-14.43, 0.06)], Mexican Americans [-6.80 (-13.63, 0.03)], and participants with BMI >30 cm2 [-10.83 (-19.70, -1.96)]. Conclusions: PIR was significantly and negatively associated with the degree of hepatic steatosis in US adolescents. Additional prospective studies are needed to confirm our findings.